2020
DOI: 10.3390/nano10061017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Antimicrobial Effects of Tungsten Nanoparticles and Tungsten Nanocomposite Fibres on Hospital Acquired Bacterial and Viral Pathogens

Abstract: A significant proportion of patients acquire hospital associated infections as a result of care within the NHS each year. Numerous antimicrobial strategies, such as antibiotics and surface modifications to medical facilities and instruments, have been devised in an attempt to reduce the incidence of nosocomial infections, but most have been proven unsuccessful and unsustainable due to antibiotic resistance. Therefore, the need to discover novel materials that can combat pathogenic microorganisms is ongoing. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…It has previously been demonstrated that the bactericidal ability of Ag-NPs is potentiated by light [ 13 ]. The photosensitization phenomenon was explored to understand the dynamic interaction between silver nanoparticles and proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that the bactericidal ability of Ag-NPs is potentiated by light [ 13 ]. The photosensitization phenomenon was explored to understand the dynamic interaction between silver nanoparticles and proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of several new types of nanomaterials has recently been demonstrated. For example, Matharu et al demonstrated the antimicrobial activity of tungsten nanoparticles and tungsten nanocomposite fibers against bacteriophage T4, Escherichia coli, and Staphylococcus aureus [ 13 ]; the antimicrobial activity of graphene nanoparticles was also recently demonstrated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metals such as silver (Ag), [122][123][124][125][126] copper (Cu), 84,85,87,127,128 zinc oxide (ZnO), 95,128 tungsten oxide/carbide, 94,129,130 magnesium peroxides, 91 and their combinations are employed as AMA in fabrics or face masks.…”
Section: Metal and Metal Oxidesmentioning
confidence: 99%
“…Figure 8 UV-C radiation effect on SARS-COV-2 [11] In conclusion, UV-C is very useful for disinfecting water, building air, transportation, and the surfaces of different objects or products. UV-C is effective for all microorganism species: bacteria, viruses, and fungi.…”
Section: Why Uv-c For Air Disinfection?mentioning
confidence: 99%